(3QSGdI eNJUQI aj GdMSGHs
(3ChdgG (B:s
(3GdMSGH Ydi JYde Hg GdeMUhdGJ GdYOOjI hGdYOO LeGYI GMGO hGdhGMO eGdGjfbSe HGdfbd hdG HGdbhI s
(3BNQgG (B:s
(3Ke GLeY GdMhGUd GdCQHY CYfi KdKeGFI hNeSjf hJSYjf hNeSg YTQ jHdZ CQHYeGFg hNeSI hNeSjf hgh GdLhGH hGddg CYde HGdUhH s
(3YdjgG bQGAI SfI (B773s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi (B(1/7189) s
Keywords: (3GdQjGVjGJs